2017
DOI: 10.1115/1.4038063
|View full text |Cite
|
Sign up to set email alerts
|

Buckling of a Pressurized Hemispherical Shell Subjected to a Probing Force

Abstract: We study the buckling of hemispherical elastic shells subjected to the combined effect of pressure loading and a probing force. We perform an experimental investigation using thin shells of nearly uniform thickness that are fabricated with a well-controlled geometric imperfection. By systematically varying the indentation displacement and the geometry of the probe, we study the effect that the probe-induced deflections have on the buckling strength of our spherical shells. The experimental results are then com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 28 publications
4
44
0
1
Order By: Relevance
“…While the experimental studies by Marthelot et al [2017] and Virot et al [2017] applied probing with a one-sided force (the poker in figure 10 pushes but cannot pull), the numerical results in figures 1, 3 and 5 extend the equilibrium surface for the probed shell to negative probe forces, achievable, for example, by gluing the poker to the shell (as proposed in the introduction). Gluing corresponds to a two-sided clamp, prescribing the displacement of the shell at the probed point.…”
Section: General Controllability Through Probingmentioning
confidence: 99%
See 4 more Smart Citations
“…While the experimental studies by Marthelot et al [2017] and Virot et al [2017] applied probing with a one-sided force (the poker in figure 10 pushes but cannot pull), the numerical results in figures 1, 3 and 5 extend the equilibrium surface for the probed shell to negative probe forces, achievable, for example, by gluing the poker to the shell (as proposed in the introduction). Gluing corresponds to a two-sided clamp, prescribing the displacement of the shell at the probed point.…”
Section: General Controllability Through Probingmentioning
confidence: 99%
“…For the pressurized hemi-sphere subject to the displacement-controlled probing, a dimple buckle forms under the probe confined to the vicinity of the pole prior to collapse. Curves of experimentally measured probe force versus probe displacement for 11 values of prescribed pressure from Marthelot et al [2017] are shown in Fig. 7 for a shell with R/t = 119 which buckled under pressure alone at p/p C = 0.74.…”
Section: Experiments On Spherical Shellsmentioning
confidence: 99%
See 3 more Smart Citations